Answer:
The answer is 12a^3+2a²+23a+18 ....
Step-by-step explanation:
The given terms are:
(3a + 2)(4a² - 2a + 9)
Now multiply each value of second bracket with the first bracket:
=4a²(3a+2) -2a(3a+2)+9(3a+2)
=12a^3+8a²-6a²-4a+27a+18
Solve the like terms:
=12a^3+2a²+23a+18
Therefore the answer is 12a^3+2a²+23a+18 ....
Answer:
10
Step-by-step explanation:
Answer:
k = 2
Step-by-step explanation:
Use a graphing calculator
Answer:
128°
Step-by-step explanation:
x + 154° + 78° = 360° {being complete turn}
x + 232° = 360°
x = 360° - 232°
x = 128°
Answer:
-6x + 17
Step-by-step explanation:
-(6x - 17)
= -6x + 17
=》Negative × negative = positive
=》 Positive × negative = negative
Hope it helps ⚜